Craniofacial morphology of children with complete unilateral cleft lip and palate following labioplasty and palatoplasty - Sigit Handoko Utomo; Krisnawati Krisnawati; Benny M. Soegiharto (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: A complete unilateral cleft lip and palate generally results in asymmetry of the midface. The lack of continuity in the perilabial musculature through the midline contributes to a malpositioning of the underlying osseus structures which are often underdeveloped. Purpose: The purpose of this study was to determine whether there are differences in the craniofacial morphology among children with complete unilateral cleft lip and palate following labioplasty and palatoplasty as compared with children without cleft lip and palate at the same pubertal age. Methods: A series of 14 consecutively treated subjects with complete unilateral cleft lip and palate following labioplasty and palatoplasty were compared with 14 pubertal stage-matched controls with normal craniofacial structure. Pubertal stage was determined with cervical vertebral maturation (CVM) method improved by Baccetti et al, 2002. Lateral cephalograms were used for comparison. An unpaired t-test was run for 14 subjects with complete unilateral cleft lip and palate and 14 normal subjects. Results: There were significant cephalometric differences in anterior cranial base length (p = .002), cranial base length (p = .001), maxillary length (p = .000), mandibular length (p = .000), mandibular ramus height (p = .000), mandibular body length (p = .002), and upper anterior face height (p = .004). There was no significant cephalometric difference in posterior cranial base length (p = .051), lower anterior face height (p = .206), posterior face height (p = .865), growth pattern/ facial type (p = .202). Conclusion: There were craniofacial morphology differences between children with complete unilateral cleft lip and palate post labioplasty and palatoplasty and children without cleft lip and palate at the age of pubertal. Children with complete unilateral cleft lip and palate post labioplasty and palatoplasty had shorter length of the anterior cranial base, cranial base, maxilla, mandible, mandibular ramus height, mandibular body, and upper anterior face height as compared with children without cleft lip and palate at the age of pubertal.Latar belakang: Celah bibir dan langit-langit unilateral komplit umumnya menghasilkan asimetri wajah bagian tengah. Berkurangnya kontinuitas otot di sekitar bibir yang melewati garis tengah wajah mengakibatkan malposisi struktur tulang di bawahnya yang seringkali kurang berkembang. Tujuan: Tujuan penelitian ini adalah untuk menentukan apakah terdapat perbedaan morfologi kraniofasial anak dengan celah bibir dan langit-langit unilateral komplit pasca labioplasti dan palatoplasti dibandingkan anak tanpa celah bibir dan langit-langit pada usia pubertal. Metode Penelitian: Sejumlah subyek penelitian berupa 14 orang anak penderita celah bibir dan langit-langit pasca labioplasti dan palatoplasti dibandingkan dengan 14 orang anak yang normal pada masa pubertal yang sama. Masa pubertal ditentukan menggunakan metode cervical vertebral maturation (CVM) yang dikembangkan oleh Baccetti dkk, 2002. Dilakukan perbandingan hasil pengukuran sefalogram lateral dari kedua kelompok. Uji-t tidak berpasangan dilakukan untuk mengetahui perbedaan gambaran kraniofasial antara kelompok anak dengan celah bibir dan langit-langit unilateral komplit pasca labioplasti dan palatoplasti dan kelompok anak normal. Hasil: Terdapat perbedaan bermakna pada panjang basis kranium anterior (p = .002), panjang keseluruhan basis kranium (p = .001), panjang maksila (p = .000), panjang mandibula (p = .000), tinggi ramus mandibula (p = .000), panjang badan mandibula (p = .002), tinggi wajah anterior atas (p = .004). Tidak terdapat perbedaan bermakna pada panjang basis kranium posterior (p = .051), tinggi wajah anterior bawah (p = .206), tinggi wajah posterior (p = .865), pola pertumbuhan/tipe wajah (p = .202). Kesimpulan: Terdapat perbedaan morfologi kraniofasial antara anak dengan celah bibir dan langit-langit unilateral komplit pasca labioplasti dan palatoplasti dibandingkan anak tanpa celah bibir dan langit-langit pada masa pubertal. Anak dengan celah bibir dan langit-langit unilateral komplit pasca labioplasti dan palatoplasti memiliki panjang basis kranium anterior, panjang keseluruhan basis kranium, panjang maksila, panjang mandibula, tinggi ramus mandibula, panjang badan mandibula, dan tinggi wajah anterior atas yang lebih pendek dibandingkan anak tanpa celah bibir dan langit-langit pada masa pubertal.